2018
DOI: 10.1007/s11118-018-9721-7
|View full text |Cite
|
Sign up to set email alerts
|

Carathéodory Convergence and Harmonic Measure

Abstract: We give several new characterizations of Carathéodory convergence of simply connected domains. We then investigate how different definitions of convergence generalize to the multiply-connected case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…By assumption, D \ F n → D \ F ∞ as n → ∞ in Carathéodory's sense. Then these domains have "arbitrarily good common interior approximations" by the implication (i) ⇒ (ii) in Theorem 2.3 of Binder, Rojas and Yampolsky [2]. Although this theorem assumes the simple connectivity, the implication needed here remains valid even if domains are not simply connected.…”
Section: Uniform Regularity Of Domainsmentioning
confidence: 85%
See 2 more Smart Citations
“…By assumption, D \ F n → D \ F ∞ as n → ∞ in Carathéodory's sense. Then these domains have "arbitrarily good common interior approximations" by the implication (i) ⇒ (ii) in Theorem 2.3 of Binder, Rojas and Yampolsky [2]. Although this theorem assumes the simple connectivity, the implication needed here remains valid even if domains are not simply connected.…”
Section: Uniform Regularity Of Domainsmentioning
confidence: 85%
“…The merit of our method is that the hitting probability of the ABM to a hull F is given by the harmonic measure of H \ F . In fact, Binder, Rojas and Yampolsky [2] showed that the Carathédory convergence implies the weak convergence of harmonic measures under certain assumptions. Their result plays a central role in the proof of (1.3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…x at a single point x = x 0 ∈ Ω is sufficient to guarantee the existence of such an algorithm for any other point x in the domain Ω. The proof of this theorem is based on a new concept of harmonic approximation of domains, which builds on the ideas of another work of the subset of the authors [3]. We show that having an algorithm for approximating a domain harmonically is equivalent to being able to compute all of its harmonic measures.…”
Section: Introduction 1motivationmentioning
confidence: 92%
“…It was proven in [3] that for simply connected planar domains the weak convergence of harmonic measures is equivalent to the classical Carathéodory convergence. In light of these results, it is not surprising that the condition of Theorem F is exactly the same as the condition for the existence of computable Riemann bijection in Computable Riemann Mapping Theorem (see [5]).…”
Section: Introduction 1motivationmentioning
confidence: 99%